THE INFLUENCE OF CHIEF EXECUTIVE OFFICER INDIVIDUAL FACTORS ON CAPITAL STRUCTURE - Thomas Yulianto Prakoso; Putu Anom Mahadwartha; Arif Herlambang (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
This study aims to analyze the effect of Chief Executive Officer (CEO) individual factor towards capital structure decision using Leverage as a dependend variable with Age (CEO Age), Tenure as independen variable amd Capex, ROA (Return on Asset), dan IO (Institutional Ownership) as control variable on LQ45 companies listed in Indonesia Stock Exchange (BEI) in the period 2012-2016. This research uses quantitative approach with single regression analysis model. This study uses sample of firms which are listed on LQ45 in IDX on 2012 - 2016. The number of final samples used in this study were 66 business entities with 330 observations. The study findings suggest that Age and ROA variables have negative and significant effect towards Leverage, while Tenure and IO variable have positive and significant effect towards Leverage. On the other hand, Capex variables does not indicate significant effect towards Leverage in LQ45 companies on the period 2012-2016.